2018
DOI: 10.1177/1756286418783708
|View full text |Cite
|
Sign up to set email alerts
|

The meningeal and choroidal infiltration routes for leukocytes in stroke

Abstract: Stroke is a major health burden as it is a leading cause of morbidity and mortality worldwide. Blood flow restoration, through thrombolysis or endovascular thrombectomy, is the only effective treatment but is restricted to a limited proportion of patients due to time window constraint and accessibility to technology. Over the past two decades, research has investigated the basic mechanisms that lead to neuronal death following cerebral ischemia. However, the use of neuroprotective paradigms in stroke has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 113 publications
3
43
0
3
Order By: Relevance
“…In addition, a study in C57BL/6 mice revealed that M2-like macrophages were able to infiltrate the ischaemic hemisphere via the choroid plexus-cerebrospinal fluid (CSF) route, thus suggesting that autologous transplantation of M2-like microglia into the CSF might be a promising treatment strategy for ischaemic stroke [158]. Apart from the epithelial cells of the choroid plexus, there are two other routes for leukocyte migration from the blood into the brain parenchyma, i.e., BBB and the meningeal blood circulation, each of which could be exploited by microglia [159,160].…”
Section: Cellular Therapies For Stroke That Target Microgliamentioning
confidence: 99%
“…In addition, a study in C57BL/6 mice revealed that M2-like macrophages were able to infiltrate the ischaemic hemisphere via the choroid plexus-cerebrospinal fluid (CSF) route, thus suggesting that autologous transplantation of M2-like microglia into the CSF might be a promising treatment strategy for ischaemic stroke [158]. Apart from the epithelial cells of the choroid plexus, there are two other routes for leukocyte migration from the blood into the brain parenchyma, i.e., BBB and the meningeal blood circulation, each of which could be exploited by microglia [159,160].…”
Section: Cellular Therapies For Stroke That Target Microgliamentioning
confidence: 99%
“…Specifically, human senescent cells up-regulate MICA, and ULBP2, ligands for the stimulatory receptor NKG2D (Antonangeli et al, 2019). Given the CNS is under immune privilege, T-cells, NKs, and peripheral macrophages normally have limited access to the meninges and choroid plexus and far-limited access to the CNS parenchyma (Galea et al, 2007;Korin et al, 2017;Benakis et al, 2018). Thus, regardless of which CNS cell types undergo senescence, the clearance of senescent cells is likely limited in healthy non-aged individuals.…”
Section: Senescence Immune Surveillance and Immune Privilegementioning
confidence: 99%
“…In the past few years, research on anti-inflammatory strategies for stroke has focused on limiting the transendothelial migration of peripheral immune cells into the brain parenchyma, aiming to reduce stroke severity. These studies are based on the idea of endothelial transmigration of peripheral immune cells through the BBB, but new evidence suggests that there are other pathways at least just as important (if not more): migration through the meninges and choroid plexus (ChP), (for a complete review, see ( Benakis et al, 2018 ).…”
Section: Experimental Basis For the Clinical Trials On Immunomodulatomentioning
confidence: 99%
“…However, VCAM as well as ICAM-1 are not expressed on ChP EC ( Steffen et al, 1996 ). Hence, lymphocytes in the ChP vasculature have no access to these adhesion molecules and blocking of these will not affect the ChP infiltration route ( Benakis et al, 2018 ). In contrast, Fingolimod works by promoting lymphocyte retention in the thymus and lymph nodes ( Mandala et al, 2002 ) and thus reduces the number of circulating lymphocytes independently of adhesion molecules expression at the various migration routes, which might explain why currently the only positive results on treatment efficacy are obtained with this drug in patients with stroke ( Benakis et al, 2018 ).…”
Section: Experimental Basis For the Clinical Trials On Immunomodulatomentioning
confidence: 99%